Holistic approach to restore marine ecosystems: RENOVATE project - Marco Marcelli; Sergio Scanu; Daniele Piazzolla; Simone Bonamano; Alice Madonia; Giorgio Fersini; Viviana Piermattei; Mar Bosch-Belmar; Francesco Paolo Mancuso; Giulia Ceccherelli; Annalisa Falace; Paola Del Negro; et al. (Frontiers in Marine Science, 2026)
Mediterranean coastal ecosystems are increasingly threatened by multiple anthropogenic pressures and climate change. As a result, these impacts have caused the decline of key endemic habitats such as Posidonia oceanica meadows and coralligenous reefs. Due to the slow natural recovery of these habitats after degradation, restoration actions play a key role in accelerating ecosystem recovery, reestablishing ecological structure and functional processes, and preventing further biodiversity and ecosystem service loss. Given the frequent habitat fragmentation and high levels of endemism, effective restoration efforts require a multidisciplinary, ecosystem-based approach that integrates marine science, engineering, socioeconomics, and policy. This study describes the holistic approach adopted in the RENOVATE project, which established an integrated framework to address the combined impacts of climate change and human pressures on vulnerable ecosystems. The framework employs advanced observational technologies, field data, and numerical modeling within an adaptive management loop, enabling site-specific, evidence-based restoration planning and assessment of ecosystem services recovery. Additionally, the study reports results from the northern Tyrrhenian coast (Latium, Italy), where RENOVATE aims to protect EU priority habitats and species from human pressures and climate-related threats. Although project activities are still in early stages, results from active restoration in the northern Latium coast show initial establishment and survival at pilot sites, highlighting the framework’s potential to guide effective, replicable interventions in coastal ecosystems. Beyond the regional case study, the proposed framework contributes to global marine restoration efforts by providing a transferable methodology for the management of coastal ecosystems.

Multi-decadal evolution of the Moroccan Atlantic shoreline: A case study from the Essaouira coastal sector - Saadia Lharti; Germán Flor; Sahar El kasmi; Germán Flor-Blanco; M'hamed El Janati; Marco Marcelli; Daniele Piazzolla; Sergio Scanu; Giancarlo Della Ventura; Boubker Boukili; Nacir El Moutaoukkil (Journal of African Earth Sciences, 2024)

River–coastal–ocean continuum modeling along the Lazio coast (Tyrrhenian Sea, Italy): Assessment of near river dynamics in the Tiber delta - Simone Bonamano; Ivan Federico; Salvatore Causio; Viviana Piermattei; Daniele Piazzolla; Sergio Scanu; Alice Madonia; Nicola Madonia; Giovanni De Cillis; Eric Jansen; Giorgio Fersini; Giovanni Coppini; et al. (Estuarine, Coastal and Shelf Science, 2024)

Mapping small‐scale fisheries through a coordinated participatory strategy - Fabio Grati; Ernesto Azzurro; Martina Scanu; Anna Nora Tassetti; Luca Bolognini; Stefano Guicciardi; Sergio Vitale; Danilo Scannella; Pierluigi Carbonara; Branko Dragičević; Zdravko Ikica; Arian Palluqi; et al. (Fish and Fisheries, 2022)
The knowledge of small‐scale fisheries (SSFs) is important to develop management policies and mitigate the competition for marine resources. However, spatially explicit information is often unavailable at the regional and subregional scale. We designed and tested a novel participatory approach to map the SSF fishing effort using the Mediterranean sea as a case study. We applied the approach in eight countries (Albania, Croatia, Italy, Libya, Malta, Montenegro, Slovenia and Tunisia) characterized by different cultural, social, political and ecological features. The results provided quantitative and spatially explicit information on fishing operations on a fine‐scale resolution, contributing to overcome the pragmatic and budgetary constraints that to date have prevented an accurate assessment of SSFs worldwide. This novel participatory approach is inspired by the principles of governance, adaptive management, cross‐national cooperation and spatial planning, thus supporting the ecosystem approach to fisheries and has the potential to provide a useful complement to traditional assessments.

Trace-metal distribution and ecological risk assessment in sediments of a sheltered coastal area (Gulf of Gaeta, central-eastern Tyrrhenian Sea, Italy) in relation to hydrodynamic conditions - SIMONE BONAMANO; DANIELE PIAZZOLLA; SERGIO SCANU; VIVIANA PIERMATTEI; MARCO MARCELLI (Mediterranean Marine Science, 2021)
This study investigates the relationship between sediment contamination and hydrodynamic conditions in the Gaeta Gulf (Tyrrhenian Sea, Italy), an anthropogenically impacted and sheltered coastal area. The pollution levels, potential toxicity, and ecological risk of trace metals were analysed in 16 sediment sampling sites using Sediment Quality Guidelines (SQGs), the Adverse Effect Index (AEI), and the Mean ERM Quotient (m-ERM-Q). The bottom shear stress of the study area, evaluated using an annual simulation of a 3D numerical model, was used to calculate a new Sediment Mobilisation Index (SMI) that detects the coastal zones where a low probability of sediment resuspension occurs. As, Ni, and Cu concentrations exceeded the Threshold Effects Level (TEL) guideline value and AEI limit in several sampling sites, indicating their ability to produce adverse effects on biota. Moreover m-ERM-Q showed the highest values of potential ecological risk in most of the sampling sites located in the inner part of the Gulf of Gaeta. In this area, the highest SMI values were also identified, demonstrating that there is a tight relationship between the two indexes (R2 = 0.8214). The application of SMI in sheltered areas will help achieve high performance of monitoring and hazard assessment tools through obtaining predictable responses on hotspot identification.

Preliminary Investigation of Microlitter Pollution in Low-Energy Hydrodynamic Basins Using Sabella spallanzanii (Polychaeta: Sabellidae) Tubes - Daniele Piazzolla; Valentina Cafaro; Emanuele Mancini; Sergio Scanu; Simone Bonamano; Marco Marcelli (Bulletin of Environmental Contamination and Toxicology, 2020)

Mercury Enrichment in Sediments of the Coastal Area of Northern Latium, Italy - Sergio Scanu; Daniele Piazzolla; Francesco Manfredi Frattarelli; Emanuele Mancini; Francesco Tiralongo; Maria Violetta Brundo; Daniele Tibullo; Roberta Pecoraro; Chiara Copat; Margherita Ferrante; Marco Marcelli (Bulletin of Environmental Contamination and Toxicology, 2016)

Where is the best site for wave energy exploitation? Case study along the coast of northern Latium (ITALY) - Francesco Paladini de Mendoza; Simone Bonamano; Giuseppe Stella; Monica Giovacchini; Dario Capizzi; Fulvio Fraticelli; Sergio Muratore; Calogero Burgio; Sergio Scanu; Maximo A. Peviani; Marco Marcelli (Journal of Coastal Conservation, 2016)

Trace-Metal Enrichment and Pollution in Coastal Sediments in the Northern Tyrrhenian Sea, Italy - Daniele Piazzolla; Sergio Scanu; Francesco Manfredi Frattarelli; Emanuele Mancini; Francesco Tiralongo; Maria Violetta Brundo; Daniele Tibullo; Roberta Pecoraro; Chiara Copat; Margherita Ferrante; Marco Marcelli (Archives of Environmental Contamination and Toxicology, 2015)